Review of Mahvash Ghavimi’s Retranslations from Two of Camus's Plays - Masoumeh Zavarian; Mahdi Mohammad Beighy (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Mahvash Ghavimi, a researcher,  university professor, and one of the famous experts in French language and literature, whose main fame in translation is related to the works of Christian Bobin, has translated Le Malentendu and Les Justes by Albert Camus. Ashian Publishing published both of them in 2010 in a volume, then republished them in 2018. In the present article, we have a brief look at the paratextuality, approaches to translating the play and its problems, the background of the translation of these two works in Iran and reason for retranslation. We also examined these two plays from a textual perspective and tried to take an overview to a translation approach in these two works. The discussion of the performance, which is the fundamental element of any play, is detailed and does not fit into this paper and is left to the experts in this field. In the translation of these two works, the content of the original text has been translated and conveyed as far as it is intended, but regardless of its performance in terms of text, sometimes the haste and the translation of the word to the word are obvious.